The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1017/s1742758400014107
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal bionomics of Heliothis armigera (Hubner) (Lepidoptera: Noctuidae) in the Terai Belt of northeastern Uttar Pradesh

Abstract: bstract-Heliothis armigera (Hubner) completed five generations in the laboratory, as well as in the field, in a year. The first generation was completed from the first week of December to the fourth week of February, the second generation from the second week of February to first week of April. The third generation from third week of August passing through the extreme summer, the fourth generation during monsoon period and the fifth last generation from the third week of September to the fourth week of Novembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…Laboratory experiments on Sudanese H.armigera have also shown that when, some 80 days after pupation, diapausing insects are subjected to a temperature rise from 22°C to 34"C, 8% of the pupae remain in diapause for a further 2 months and only resume development when the temperature is lowered again (Hackett & Gatehouse, 1982). Similar results have been obtained for north Indian H.armigera (Tripathi & Singh, 1993). In both cases it was proposed that this enabled insects both to survive the hot dry season and to synchronize emergence with the beginning of the rains.…”
Section: Discussionsupporting
confidence: 77%
“…Laboratory experiments on Sudanese H.armigera have also shown that when, some 80 days after pupation, diapausing insects are subjected to a temperature rise from 22°C to 34"C, 8% of the pupae remain in diapause for a further 2 months and only resume development when the temperature is lowered again (Hackett & Gatehouse, 1982). Similar results have been obtained for north Indian H.armigera (Tripathi & Singh, 1993). In both cases it was proposed that this enabled insects both to survive the hot dry season and to synchronize emergence with the beginning of the rains.…”
Section: Discussionsupporting
confidence: 77%
“…Its population peaks generally correspond to the full bloom and pod formation stage of the crop in the post rainy season. Temperature, relative humidity Lal 1988, Yadava et al, 1991), rainfall (Tripathi and Sharma 1985), predators (Thakur et al, 1995, Gunathilagaraj 1996 and parasitoids (Bhatnagar 1980, Srinivas and Jayaraj 1989, Thakur et al, 1995 affect the incidence and population densities of H. armigera on chickpea. Information on pest incidence under field conditions across sowing dates can be used to assess the effect of different climatic variables on pest incidence and grain yield.…”
Section: Issn: 2319-7706 Volume 8 Number 09 (2019)mentioning
confidence: 99%
“…The H. armigera larvae found active throughout the chickpea crop (Singh and Ali, 2006). The ecological parameters viz., temperature o C), photoperiod (10-14 hrs), relative humidity (15-95%) coupled with optimal and intermittent rainfall were found to influence the population buildup, adult emergence and maximum fecundity of the female moths of H. armigera (Tripathi and Singh, 1993). The pest could be managed naturaly under field conditions by larval parasitoid Campoletis chlorideae Uchida (Hymenoptera: Ichneumonidae) in chickpea ecosystem, causes up to 78% parasitisation of early instars under natural conditions (Agnihotri et al, 2011).…”
Section: Introductionmentioning
confidence: 99%